Police Efforts in Handling Violent Crimes Committed by Students in Groups: a Case Study at Pancur Batu Police Station - Aldi Suprianto; Rizkan Zulyadi (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2025)
Incidents of violence among students, particularly those involving groups operating beyond the reach of law enforcement, continue to occur frequently. The police must implement proactive preventive measures to avoid such incidents, as these behaviors contradict the norms that students are expected to uphold. The importance of appropriate handling of students involved in crime and violence, particularly from a law enforcement perspective, is highly emphasized. This study addresses the following problems: what are the factors that cause group violence committed by students within the jurisdiction of the Pancur Batu Police Sector; how is the legal regulation regarding criminal acts of violence committed by minors; and what efforts are being undertaken by the police in addressing the issue. This research is an empirical legal study. The data analysis applied in this research follows a qualitative approach. The results conclude that the occurrence of student brawls is not only driven by personal desire but is also heavily influenced by peer pressure, which significantly affects one's social interactions and behavior. Legal provisions governing violent crimes committed by students can be found in the Indonesian Criminal Code, particularly Articles 170, 351, and 406, as well as in Law Number 35 of 2014 on Child Protection. The efforts made by the Pancur Batu Police in addressing group violence among students include both preventive and repressive approaches.